2019
DOI: 10.1515/openec-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Management and the Role of Leader

Abstract: The paper’s intention is to provide the correspondence of the globalization and the diversity in the management in this current trade era. The aim of the article is to understand the leader’s role in diversity management which is rapidly changing the global trade market more clearly. Globalization has a very big influence on the diversity management these days, both directly and indirectly. This study is based on a systematic review of 14 journal articles presented on the concerned topic. It is divided into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…In the literature, no study was found in which all three variables were used together. However, it is frequently emphasized in the literature that organizations should encourage differences rather than ignore them, value the workforce from different backgrounds, and try to improve their ability to manage them, in order to gain a sustainable competitive advantage in differentiated markets ( McCann and Kohntopp, 2017 ; Rahman, 2019 ; Jankelová et al, 2020 ). Therefore, when we look at the issue from the point of view of educational organizations, having a strong sustainable leadership structure of the organization for a sustainable success will be the key to the successful management of the diversities within the institution.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, no study was found in which all three variables were used together. However, it is frequently emphasized in the literature that organizations should encourage differences rather than ignore them, value the workforce from different backgrounds, and try to improve their ability to manage them, in order to gain a sustainable competitive advantage in differentiated markets ( McCann and Kohntopp, 2017 ; Rahman, 2019 ; Jankelová et al, 2020 ). Therefore, when we look at the issue from the point of view of educational organizations, having a strong sustainable leadership structure of the organization for a sustainable success will be the key to the successful management of the diversities within the institution.…”
Section: Resultsmentioning
confidence: 99%
“…Research says if people are aware of diverse perspectives, there will be a presence of mutual respect to one another and create an atmosphere where anyone can share his/her divergent ideas, opinions, views, and perspectives (Jones & George, 2009). Further, some study also says that the dissemination of diversity awareness initiative needs to be taken by top leadership and showing commitment to inculcate throughout the organization to achieve its optimal results (Rahman, 2019). In conclusion, I predict that Bangladeshi origin firms will overcome the differences and aspire to be culturally, geographically, and economically diversified institutions.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies are available on the diversity awareness model. Still, most of these studies probably focused on managerial, executive and women's diversity and their perception towards understanding others (e.g., Miller (Rahman, 2019;Back, 1998;Gentry et al, 2014;Okoro, 2012;Chuang, 2013). The present study identifies mainly four key HR practices, i.e., employee engagement, diversity training, diversity alignment (inclusion), and mutual respect.…”
Section: Introductionmentioning
confidence: 99%
“…The systematic review and further analysis of 14 articles on the leader's role in diversity management shows that leaders or managers play a decisive role in the workplace ensuring that diversity is properly handled. This role includes education, empowerment, motivation, training, and interpersonal skills, among many others (Rahman, 2019). Leaders who engage in diversity management practices influence the relationship between diversity and the perceptions of a group's work performance (Jin et al, 2017).…”
Section: Leadership Development Programsmentioning
confidence: 99%